Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Mujari Mujari; Hestin Hestin; Kasinem Kasinem; Kandar Malian (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of price and service quality partially and simultaneously on customer satisfaction at Pondok 99 Empat Lawang Restaurant. This research method is quantitative. The population used in this research is Pondok 99 Empat Lawang Restaurant customers. The method of determining the sample in this study uses the accidental sampling method. The research data will be analyzed by using multiple linear regression analysis, F test, T test, and coefficient of determination test (RÂ²). The results showed, a) the price variable on customer satisfaction, by partial testing obtained a significant value of 0.006 <0.05; b) the variable of service quality on customer satisfaction, by partial testing obtained a significant value of 0.000 <0.05; c) with simultaneous testing, a significant value is obtained, namely 0.000 <0.05. In conclusion, price has a significant effect on customer satisfaction at Pondok 99 Empat Lawang Restaurant. Service quality has a significant effect on customer satisfaction at Pondok 99 Empat Lawang Restaurant. Price and service quality have a significant effect on customer satisfaction at Pondok 99 Empat Lawang Restaurant. Keywords: Price, Customer Satisfaction, Service Quality